Pioneering nanomedicine in orthopedic treatment care: a review of current research and practices - Liang, Wenqing; Zhou, Chao; Zhang, Hongwei; Bai, Juqin; Long, Hengguo; Jiang, Bo; Liu, Lu; Xia, Linying; Jiang, Chanyi; Zhang, Hengjian; Zhao, Jiayi (Frontiers in Bioengineering and Biotechnology, 2024)
A developing use of nanotechnology in medicine involves using nanoparticles to administer drugs, genes, biologicals, or other materials to targeted cell types, such as cancer cells. In healthcare, nanotechnology has brought about revolutionary changes in the treatment of various medical and surgical conditions, including in orthopedic. Its clinical applications in surgery range from developing surgical instruments and suture materials to enhancing imaging techniques, targeted drug delivery, visualization methods, and wound healing procedures. Notably, nanotechnology plays a significant role in preventing, diagnosing, and treating orthopedic disorders, which is crucial for patients' functional rehabilitation. The integration of nanotechnology improves standards of patient care, fuels research endeavors, facilitates clinical trials, and eventually improves the patient’s quality of life. Looking ahead, nanotechnology holds promise for achieving sustained success in numerous surgical disciplines, including orthopedic surgery, in the years to come. This review aims to focus on the application of nanotechnology in orthopedic surgery, highlighting the recent development and future perspective to bridge the bridge for clinical translation.